Highly enhanced charge injection and bulk transport in organic gap‐type diodes via one‐pot treatment process: experiment and simulation. (1st December 2014) - Kim, Hyeok; Song, Dong‐Seok; Kim, SeongMin; Battaglini, Nicolas; Lang, Philippe; Horowitz, Gilles; Kim, Do‐Kyung; Kang, In Man; Bae, Jin‐Hyuk
Abstract : The gap‐type diode is a basic component of organic field‐effect transistors. In the critical voltage range above 10 V, the gap‐type diode works in the same way as a sandwich‐type diode adapted for organic light‐emitting diodes and organic photovoltaic cells. However, the gap‐type diode is rarely studied, and compact modelling is not often found in previous reports that deal with this type of an organic diode. Enhanced bulk transport is exhibited using the one‐pot treatment of self‐assembled monolayers (SAMs) for an SiO2 surface and an Au contact metal in the gap‐type organic diode. Charge‐injection improvement via the SAM treatment on Au induces higher bulk transport. This phenomenon is analysed mainly through compact modelling.